The effect of pyrolysis conditions on biochar stability as determined by three methods. Issue 2 (21st December 2012) - Crombie, Kyle; Mašek, Ondřej; Sohi, Saran P.; Brownsort, Peter; Cross, Andrew
Abstract Biochar is the porous, carbonaceous material produced by thermochemical treatment of organic materials in an oxygen‐limited environment. In general, most biochar can be considered resistant to chemical and biological decomposition, and therefore suitable for carbon (C) sequestration. However, to assess the C sequestration potential of different types of biochar, a reliable determination of their stability is needed. Several techniques for assessing biochar stability have been proposed, e.g. proximate analysis, oxygen (O): C ratio and hydrogen (H): C ratio; however, none of them are yet widely recognized nor validated for this purpose. Biochar produced from three feedstocks (Pine, Rice husk and Wheat straw) at four temperatures (350, 450, 550 and 650 °C) and two heating rates (5 and 100 °C min−1) was analysed using three methods of stability determination: proximate analysis, ultimate analysis and a new analytical tool developed at the UK Biochar Research Centre known as the Edinburgh accelerated ageing tool (Edinburgh stability tool). As expected, increased pyrolysis temperatures resulted in higher fractions of stable C and total C due to an increased release of volatiles. Data from the Edinburgh stability tool were compared with those obtained by the other methods, i.e. fixed C, volatile matter, O : C and H : C ratios, to investigate potential relationships between them. Results of this comparison showed that there was a strong correlation (R > 0.79) between the stable C determined by the Edinburgh stability tool and fixed C, volatile matter and O : C, however, H : C showed a weaker correlation (R = 0.65). An understanding of the influence of feedstock and production conditions on the long‐term stability of biochar is pivotal for its function as a C mitigation measure, as production and use of unstable biochar would result in a relatively rapid return of C into the atmosphere, thus potentially intensifying climate change rather than alleviating it.